EDUKASI DAN PENDAMPINGAN GERAKAN CEGAH STUNTING PADA REMAJA SEBAGAI UPAYA PREVENTIF RESIKO PENYAKIT JANTUNG KORONER DI SMPN 1 KAMPAR - Sari, Septi Indah Permata; Paramita, Irma Susan; Septiana, Dewi; Atasasih, Hesti (PITIMAS: Journal of Community Engagement in Health, 2025)
Stunting is a chronic nutritional problem that impacts child growth and increases the risk of degenerative diseases, including coronary heart disease. Prevention can begin early through nutrition education, healthy breakfast habits, physical activity, and consumption of iron tablets for adolescent girls. This Community Service Program was implemented at SMPN 1 Kampar with an Interprofessional Education (IPE) approach involving nutrition and midwifery professions. The activities carried out were pre-tests, breakfast together, physical activity in the form of gymnastics, nutrition education and post-tests. The media used were PPT, leaflets, booklets and posters. Target outputs include publication of articles in scientific journals and mass media as well as educational media that have been registered with HAKI. This program is expected to be able to form healthy living habits, prevent stunting from an early age, and reduce the risk of coronary heart disease in future generations.